Enrobing Ceremony for Judges Thomas Harris, Steven Vartabedian, Edward Sarkisian, Jr. and Lawrence Jones at Fresno's Veterans Memorial Auditorium - Watkins, Howard::::::::: (1987)
Superior Court Presiding Judge Stephen Henry welcoming everyone; En Banc Court: Justices Don Franson, Wickson Woolpert, Robert Martin and Hollis Best; Judges John Fitch, Robert Mardikian, Leonard Meyers, and Stephen Vartabedian; back: Judges Dwayne Keyes, James Thaxter and others